Effect of citric acid and calcium chloride combined with medium high hydrostatic pressure – medium high temperature on polyphenol oxidase activity and browning in Fuji apple compote - Yamazaki, Shinya; Kaneko, Shoji; Takahashi, Yuta; Amano, Yoshihiko (Food Science and Technology Research, 2023)
Combined medium-high hydrostatic pressure (MHHP) and medium-high temperature (MHT) treatment is an effective process for liquid impregnation and food pasteurization. Although several fruit processing additives are known to inhibit polyphenol oxidase (PPO), the effect of additives on PPO activity after MHHP+MHT treatment has not been studied. This study describes the effect of citric acid and calcium chloride on PPO activity after MHHP+MHT treatment. The lyophilized powder of Fuji apples was subjected to MHHP+MHT treatment in a solution containing sucrose, citric acid, and calcium chloride, and residual PPO activity was measured. Combined citric acid and calcium chloride additive use reduced PPO activity more effectively than their individual use. Using this additive combination to decrease PPO residual activity in conjunction with MHHP+MHT proved to decrease apple compote browning homogeneously, which we believe will prove a useful method in preservation processes.